(3JPcQI Phj GdBOGH aj TQM edMI GdEYQGHs - (3CHheMeO GdbGSe Hf Ydj Hf eMeO Hf YKeGf GdMQjQj GdHUQjs; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3Gbhd ef HYO GaJJGM Gdbhd HMeO Pj GdWhd GdTOjO GdMhd s
(3BNQgG (B:s
(3aGfXQ EdjgG fXQ GdeSJMSf hMSf GdXf HgG hCMSf JeJ edMI GdEYQGH HTQMgG s
(3fSNI KGdKI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGX hGdYHGQGJ NGUI aj ChdgGs
(3ecedI aj ZjQ ehVY HNW MOjKs
(3HChdgG Jedc eDQN aj SfI (B1116(3g```s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs